Feng shui and lighting a comparative analysis of the principles of lighting design and the principles of feng shui in lighting - Neri, Kristine Anne V.; Mayo, Adelaida Villaraza (1995.)
Lighting is a very important aspects in designing. The principles of lighting design are usually dealt wih in the latter phase of conceptualization and designing. This should never be the case, instead lighting design should be dealt with in the pre-planning stage.Feng shui in lighting on the other hand gets the least of the attention. It is usually given less importance in the Feng Shui study. Feng Sui is a Chinese philosophy dealing with the balancing and harmonizing of man with the universe. This is the art of placement that aims to drive away bad spirits and feelings and hopes to bring in luck and fortune to spaces.Can it b possible that both of lighting designs be the same with the principles of Feng Shui in lighting? A comparative analysis shows that the Principles of lighting design is not far as from the Principles of Feng Shui in lighting. They actually can work together in enhancing and developing one another.With the mix of both, greater possibilities for better efficiency and effectivity of work performance may arise. A further study on this can raise possible chances in achieving a monumental breakthrough in Lighting Design.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Lighting, Architectural and decorative; Feng shui in interior decoration